Psychological Predictors of Precautionary Behaviors in Response to COVID-19: A Structural Model - Frías-Armenta, Martha; Corral-Frías, Nadia Saraí; Corral-Verdugo, Victor; Lucas, Marc Yancy (Frontiers in Psychology, 2021)
The first lines of defense during an epidemic are behavioral interventions, including stay-at-home measures or precautionary health training, aimed at reducing contact and disease transmission. Examining the psychosocial variables that may lead to greater adoption of such precautionary behaviors is critical. The present study examines predictors of precautionary practices against COVID-19 in 709 Mexican participants from 24 states. The study was conducted via online questionnaire between the end of March and the beginning of April 2020, when the pandemic response was in its initial stages in Mexico. The instrument included demographic items, as well as scales assessing COVID-19-resembling symptoms, empathy, impulsivity, anhedonic depression, general health practices, alcohol consumption, and COVID -19- associated precautionary behaviors. Most participants reported adopting limited social distancing or other precautionary behaviors against COVID-19. The results of a structural equations model demonstrated that COVID-19 resembling symptoms were related to impulsivity and general health behaviors. However, no direct association between precautionary behaviors and COVID-19 resembling symptoms was found. In turn, precautionary behaviors were more prevalent among participants who reported higher empathy and general health behaviors and were inhibited indirectly by impulsivity via alcohol consumption. Further, the model suggests that anhedonic depression symptoms have a negative indirect effect on precautionary behaviors via general health behaviors. Finally, impulsivity showed a negative direct effect on general health behavior. These results highlight the role general physical and mental health play on precautionary behavior and the critical importance of addressing issues such as depression, general health behaviors, and impulsivity in promoting safe actions and the protection of self and others.